Gene therapy as a therapeutic option for lipoprotein lipase deficiency - Kuivenhoven, Jan Albert (Henry Stewart Talks, 2008)
No treatment for genetic lipoprotein lipase (LPL) deficiency, This disorder has several specific characteristics which make it a feasible target for gene therapy approaches, Development of LPL transgene delivery, Use of adeno-associated virus
Archived at 2021/02/25